Penatalaksanaan Fisioterapi dengan Metode Core Stability Exercise dan Balance Exercise terhadap Peningkatan Keseimbangan Statis pada Pasien Stroke - Suciati Suciati; Putra Hadi; Ucu Suherman (Prosiding Seminar Kesehatan Nasional, 2022)
Stroke is damage that occurs in the blood vessels of the brain which is mostly caused by narrowing or blockage of the arteries (ischemic stroke) and can also be caused by abnormalities of blood vessels in the brain that break easily such as aneurysms. In general, the problems of post-stroke patients include: sensory disturbances, cognitive/memory disorders, psychiatric or emotional disorders. Sensomotor disturbances in post-stroke patients result in balance disorders including muscle weakness, decreased soft tissue flexibility, and impaired motor and sensory control. Loss of function due to impaired motor control in post-stroke patients results in loss of coordination, loss of ability to sense body balance and posture. To determine the management of physiotherapy with core stability exercise and balance exercise methods to increase static balance in stroke patients. After 5 times therapy for these patients using the Core Stability Exercise and Balance Exercise interventions, it was found that there was a significant increase in balance from the initial value. Evaluation of balance using the stand on one leg test on the first day (T1) : 8 increased on day 1 third (T5) 15. Core Stability Exercise and Balance Exercise can improve balance in stroke patients